IMPLEMENTASI IMAN DAN TAQWA DALAM KEHIDUPAN MODERN - Martono La Moane; Syarifuddin Ondeng; Saprin Saprin (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
Modern life is often filled with challenges and distractions that can test a person's faith and piety. Therefore, implementing faith and piety in everyday life is very important. This article discusses how individuals can integrate the values of faith and piety in the context of modern life. Faith is the foundation of belief in God and religious teachings. In the midst of modern life which is busy and full of pressure, maintaining a strong faith requires high awareness and commitment. One important step is to involve yourself in regular worship such as prayer, reading the Koran, and dhikr. Additionally, interacting with religious communities and getting guidance from clerics can help strengthen faith. Taqwa, on the other hand, reflects a person's piety and devotion to God. In a modern context, piety can be realized through good actions, high work ethics, and behavior based on moral principles. Maintaining integrity in business, doing good to others, and avoiding sinful acts are part of implementing piety in everyday life. The importance of combining faith and piety in modern life is to create harmony between spirituality and world life. It helps individuals cope with stress, live life meaningfully, and carry out their responsibilities with integrity. Thus, the implementation of faith and piety in modern life is the key to achieving spiritual and material prosperity in this increasingly complex world.